AGREEMENT ON AGRICULTURE AND INDONESIAN RICE IMPORT - Yuniarti, Dini (Economic Journal of Emerging Markets, 2011)
Indonesian economy has been long supported by its agriculture sector. This paper analyzes the influence of the World Trade Organization’s Agreement-on-Agriculture (AoA) to In-donesia’s rice import using a Partial Adjustment Model. The independent variables included in the model are domestic production of rice, domestic income, world rice price, domestic rice price, and a dummy variable of AoA implementation. It estimates secondary annual data from 1979 to 2007. The result suggests that domestic income, domestic price and the dummy variable have significant effects on Indonesian import rice. It also suggests that world rice price and total domestic rice production have no impact on Indonesia rice import. Keywords: Agreement-on-agriculture, world trade organization, rice import JEL classification numbers: F13, F14